Investigation on the relationship between CT numbers and marble failure under different confining pressures - Yan-Shuang Yang (De Gruyter, 2021)
Computed tomography (CT) scanning technology is helpful in investigating rock materials as it can demonstrate the micro structure of rock clearly. Conventional triaxial compression tests and the corresponding graded triaxial loading tests were carried out to investigate the complex failure mechanism of the marble at the Jinping Hydropower Station. After that CT-scanning tests were done on the loaded marble specimens. The test results show that (1) the CT numbers of the specimens have a certain statistical regularity, that is, the CT numbers of the specimens under different confining pressures satisfy the Weibull distribution, as the confining pressure increases, the mean values rise while variances decrease; (2) in the two groups of tests, the average CT numbers corresponding to the conventional triaxial tests are higher than those corresponding to the graded loading tests, but the CT number variances are lower than those of the graded loading tests; and (3) according to meso-damage mechanics, the damage variables of the rock specimens were established based on the definition of CT numbers. The calculation results show that the damage variables decrease with the increase in confining pressure, the damage variables of the rock specimens in the graded loading tests are higher than those in the conventional triaxial test, and the differences between the two loading tests have grown with the increase in confining pressure.